Stabilizing inventory management in supply chains with constraints in terms of uncertain stochastic demand - Дорофеев, Юрий Иванович; Куценко, Александр Сергеевич (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The inventory control strategy synthesis problem in the supply network with structural constraints under an uncertain stochastic demand is considered. The control law is constructed in the form of linear feedback based on mismatch between the current state and safety stock level, which is calculated on-line on the basis of censored demand data. The control problem is represented in terms of the Linear Matrix Inequalities based on the Invariant Ellipsoids method, and the control synthesis is reduced to the Semi-Definite Programming and the one-dimensional convex optimization.